Prospective, randomized, controlled trial comparing a tissue adhesive (Dermabond™) with adhesive strips (Steri-Strips™) for the closure of laparoscopic trocar wounds in children - Romero, Philipp; Frongia, Giovanni; Wingerter, S.; Holland-Cunz, Stefan (European journal of pediatric surgery, 2011)
Background: 4 methods are used in pediatric laparoscopic surgery to close trocar wounds. While tissue adhesives or adhesive strips have been shown to produce fewer wound complications and a better cosmetic result compared to trans- or only subcutaneous sutures, the choice of technique is still often based on the surgeon's personal experience. Thus, the objective of this trial was to assess the impact of tissue adhesives (Dermabond™) compared to adhesive strips (Steri-Strip™) on potential complications of wound healing, wound pain, cosmetic outcome, and patient satisfaction after laparoscopic appendectomy in children. Methods: 49 patients undergoing laparoscopic appendectomy were enrolled in this prospective randomized trial. In every patient, two 5-mm and one 10-mm port-site incision was closed either with Dermabond™ or Steri-Strip™ after placing subcuticular absorbable sutures (4–0 Vicryl™). Postoperative complications, pain, and patient satisfaction with scars were evaluated at follow-up on day 10 and day 90 after the operation using a questionnaire and a visual analogue scale (VAS). Photographs of scars taken on day 90 were evaluated on a VAS by 2 pediatric surgeons blinded to the closure method used. Results: According to the surgeons’ evaluation of the cosmetic outcome, a significant difference between the 2 groups with regard to the cosmetic score was found on day 90 of follow-up, favoring Steri-Strip™ wound closure (p<0.05). On day 10 and 90 there were no statistical differences between the 2 methods as regards the result of patient evaluations (p>0.05). Only one wound infection (4%) was observed in the Steri-Strip™ group (n=25) on day 10. At follow-up on day 90 two patients (9.1%) in the Dermabond™ group and one (4.8%) in the Steri-strip™ group complained of wound pain (p=0.52). Conclusions: Both tissue adhesives and adhesive strips are excellent “no needle” alternatives for the closure of laparoscopic port-site incisions in children. As regards cosmetic outcome, Steri-Strip™ wound closure seems to be the most suitable and is also the less expensive technique.